Islanding detection of integrated DG system using rate of change of frequency over reactive power - Kumari, B. V. Seshu; Prasad, Ambati Giri; Srilakshmi, S. Sai; Buchireddy, Karri Sairamakrishna; Reddy, Ch. Rami (Institute of Advanced Engineering and Science, 2025)
This paper offers a passive islanding detection method that is effective for distributed generation. When a distributed generator (DG) keeps a location powered even when access to the external electrical grid is lost, this circumstance is referred to as islanding. The power distribution system currently includes distributed generators (DGs), which provide inexpensive electricity and have fewer environmental impacts. Sometimes, these DGs continue to supply the nearby loads because of line outages and islands made by system separations. As a result, there are scenarios with unacceptable power quality. The islanding is identified if the result of the rate of change of frequency over reactive power exceeds the threshold value. The MATLAB test results from this study demonstrate the effectiveness of the suggested approach for different islanding and non-islanding scenarios.